PENGARUH KOMPETENSI DAN PELATIHAN TERHADAP KINERJA TENAGA MEDIS PUSKESMAS (Studi Kasus pada Puskesmas Menganti) - Wahyu Satrio Bintoro; Hadi Sunaryo; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study aims to determine the Effect of Competence and Training on the Performance of Menganti Health center. The type of research used is experimental. The data used are primary data, which was obtained using a questionnaire in the form of a questionnaire. The population that is the object of this research is all medical personnel at the Menganti health center.The data analysis technique in this study uses an instrument test consisting of validity and reliability, normality test, classic assumption test consisting of multicollinearity test and hiterokesdatisitas, multiple linear regression test and hypothesis test consisting of F test and t test.The results of data analysis show that: (1) the description shows the following (a) performance appreciated by quality and use of time (b) appreciated competencies are traits, knowledge and skills (c) training appreciated goals, trainers and material (2) Competence and training does not affect performance (3) competence does not affect performance (4) Training does not affect performance.Keywords: competence, training and performance.